An experimental study on cooling of model data center building by using eutectic phase change material in their walls - Kurt, Kubra; Öztop, Hakan Fehmi; Abu-Hamdeh, Nidal; Gur, Muhammed (Springer, 2023)
A prototype data center was created as part of this project. Lauric acid (LA), stearic acid (SA), and undecanoic acid (UA) were blended at a mass of 16%, 10%, and 32%, respectively, to be placed in the system. LA, SA, and UA thermophysical characteristics were examined. The melting temperatures and latent heat values of LA, SA, and UA were determined by differential scanning calorimetry to be 17.13 degrees C, 71.9 degrees C, 26.82 degrees C, and 24.49 degrees C, respectively, and 190 J g(-1), 235 J g(-1), 178 J g(-1), and 150 J g(-1). Thermal conductivities measured with the KD2 Pro were 0.288 W mK(-1) for LA, 0.143 W mK(-1) for SA, 0.201 W mK(-1) for UA, and 0.245 W mK(-1) for LA-SA-UA. The heat capacity values for LA, SA, UA, and LA-SA-UA were found to be 22.15 J g(-1), 18.82 J g(-1), 17.20 J g(-1), and 20.49 J g(-1), respectively. The findings demonstrate the utility of the LA-SA-UA mixture in energy storage. Thermocouples are deployed in the system at predetermined locations to compare the conditions when the data center is empty and with PCM. At four different speeds (5 m s(-1), 4.45 m s(-1), 4.25 m s(-1), and 2.5 m s(-1)), empty and PCM cases were compared. 5 m s(-1), 4.45 m s(-1), 4.25 m s(-1), and 2.5 m s(-1) PCM system timings were 7800-16440 s, 6960-14,200 s, 5880-11900 s, 4440 s, and 9360 s, respectively. The presence of LA-SA-UA energy storage in the data center is demonstrated in this study.
Keywords: Data Center; Energy storage; Eutectic phase change material; DSC